Maleriet og den ny krop - fire nordiske kunstnere 1900-1914 - Nielsen, Niels Kayser (Forum for Idræt, 1999)
Kunsten og maleriets fortolkning af kroppen i begyndelsen af 1900-tallet. Artiklen beskriver kunstnerens fremstilling af mandekroppen som et æstetisk objekt ofte med naturen som motiv. Nordic Painters and the new Body. The thesis of this article is that in the period around the turn of the century there was a decisive new departure in the perception of time and space in Nordic countries. This was expressed in the very movement of the body in time and space, in the areas of sport and physical exercise amongst others. It is also true of the representations of such movements, that is to say in literature and art. The article interprets the new knowledge of the being and the living space of the body in the years after 1900, including its relation to the pictorial arts. Of the Nordic painters who took sport and the body as their theme, four have been selected here. In Norway, Edvard Munch was working his way out of the straitjacket of self-obsession during the years around 1910 and for that reason became for a short period sun-worshipper and vitalist. Between 1910-12 Magnus Enckell from Finland painted a series of outdoor pictures full of lyricism and light depicting naked people on the margin between land and water. J.F.Willumsen travelled from Denmark to southern Italy in 1902 to create a set of photographs of naked boys bathing, which he later translated to large-scale oil paintings. Finally, there is Eugène Jansson from Sweden, perhaps the greatest sports enthusiast of them all. After 1910 he became increasing interested in power sport as a motif, exploring the compositional possibilities of the body and its ability to provide variation and harmony. The article demonstrates a marked difference in the perception of the body and its movement in the work of these four painters. At the same time there is a fundamental similarity in their enthusiastic and at the same time fearful fascination for corporeality and its new incarnation, which is so characteristic for the first two decades of the 20th century.